Leishmaniasis - Surprise from the East - I.V. Bogadelnikov; Yu.V. Vyaltseva; I.Z. Karimov; A.A. Degtyaryova; E.R. Mazinova; Ye.N. Dyadyura; N.G. Los'-Yatsenko (Zaslavsky O.Yu., 2012)
The clinical case of cutaneous leishmaniasis in a 4-year-old child is presented in the article. The child came to the Crimea from area where leishmaniasis is endemic - Republic of Uzbekistan. Clinical case is interesting for consideration in terms of differential diagnosis of specific rash.